From Laboratory Studies to the Field Applications of Advanced Oxidation Processes: A Case Study of Technology Transfer from Switzerland to Burkina Faso on the Field of Photochemical Detoxification of BiorecalcitrantChemical Pollutants in Water. (9th June 2009) - Kenfack, S.; Sarria, V.; Wéthé, J.; Cissé, G.; Maïga, A. H.; Klutse, A.; Pulgarin, C.
Abstract : The Fenton and photo-Fenton detoxification of non-biodegradable chemical pollution in water was investigated under simulated UV light in the laboratory and under direct sunlight in Ouagadougou, Burkina Faso. The laboratory experiments enable one to make a systematic diagnosis among three types of wastewaters, identifying a biorecalcitrant wastewater containing the Chloro-hydroxy-Pryridine (CHYPR). The application of the photo-Fenton process on effluent containing the CHYPR showed not to stimulate the generation of biodegradable by-products. Optimal conditions for detoxification of effluent containing the CHYPR were found atpH = 2.8, [ Fe 2 + ] = 5.2  mM, initial[ H 2 O 2 ] = 768  mM, for an effluent concentrated at 2.2 mM of CHYPR. The application of the photochemical process on a field pilot solar photoreactor for the detoxification of water polluted with a pesticide made with Endosulfan showed very promising results, with potential biodegradable effluents obtained at the end of the photochemical treatment. Optimal conditions of the applied study were found atpH = 3 .[ H 2 O 2 ] = 8  mM and[ Fe 2 + ] = 0.18  mM for an initial concentration of 0.36 mM of Endosulfan.